Farm-scale evaluation of two widely used sanitation practices for reducing primary inoculums of apple scab in organic apple production - Holb, I. J.; Rózsa, A.; Abonyi, F. (International Journal of Horticultural Science, 2013)
Effects of two widely used sanitation practices were evaluated at farm-scale level on leaf degradation and primary infection by Venturia inaequalis in an organic apple orchard (Eperjeske) on two apple cultivars (Jonathan and Prima) from 2011 to 2013. The tested sanitation practices were eradication of fallen leaves by collection and disc cultivation. Treatments of eradication of fallen leaves by collection and disc cultivation reduced signifi cantly (P< 0.001) leaf litter density with 70–85 and 40–55%, respectively, compared to untreated plots in both years. Above treatments in the same order reduced spring scab incidence with 40–50, and 10–20%, respectively, compared to untreated plots. Incidence of leaf scab in autumn was not signifi cantly lower (P< 0.05) in the treatments in the years.